2015
DOI: 10.5006/1709
|View full text |Cite
|
Sign up to set email alerts
|

Role of Thiosulfate in the Corrosion of Steels: A Review

Abstract: Thiosulfate salts have been known to be dangerous corrosion promoters for over 30 years, when present under typical service conditions. This paper reviews the role of thiosulfate anion in causing localized corrosion and/or stress corrosion cracking of steels. Electrochemical and mechanical aspects associated with the pitting and stress corrosion cracking of steels in thiosulfate-containing environments are thoroughly discussed and reviewed. In particular, results

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 103 publications
3
88
0
Order By: Relevance
“…Instead, previous studies have consistently identified fermentative Halanaerobium taxa as dominant colonizing microorganisms across different wells and shale plays (3, 5, 9, 10). In some instances, Halanaerobium strains may account for up to 99% of the relative abundance of the microbial community and are almost always detected as persisting key members in produced fluids (3, 4, 812).…”
Section: Introductionmentioning
confidence: 91%
“…Instead, previous studies have consistently identified fermentative Halanaerobium taxa as dominant colonizing microorganisms across different wells and shale plays (3, 5, 9, 10). In some instances, Halanaerobium strains may account for up to 99% of the relative abundance of the microbial community and are almost always detected as persisting key members in produced fluids (3, 4, 812).…”
Section: Introductionmentioning
confidence: 91%
“…Cr 3+ peaks are observed at 577.6 and 576.1 eV (Fig. 7c), which refer to Cr(OH) 3 and Cr 2 S 3 respectively. Fig.…”
Section: CLmentioning
confidence: 99%
“…Therefore, in thiosulfate-only solution, the increased current may attributed to thiosulfate species to oxidize to tetrathionates or other high oxidation state sulfur species. In addition, the E-pH diagram of S-H 2 O system shows that thiosulfate species may oxidize to HSO 3 − at high potential. Fig.…”
Section: Concentration Of Chloride Concentration Of Thiosulfatementioning
confidence: 99%
See 1 more Smart Citation
“…The dissolution of carbon steel in contact with wet ammonium chloride (NH 4 Cl) is reported to be very aggressive at higher concentrations, nearly approaching to corrosion via hydrochloric acid . However, in synergy with sulfur species such as hydrogen sulfide, thiosulfate, polysulfides, etc., corrosion is found to be even more rapid and stringent …”
Section: Introductionmentioning
confidence: 99%